2022
DOI: 10.3390/ph16010019
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of Diosmin-Loaded Diphenylcarbonate-Cross-Linked Cyclodextrin Nanosponges for Breast Cancer Therapy

Abstract: In the current study, diosmin (DSM)-loaded beta-cyclodextrin (β-CD)-based nanosponges (NSPs) using diphenylcarbonate (DPC) as a cross-linker were prepared. Four different DSM-loaded NSPs (D-NSP1-NSP4) were developed by varying the molar ratio of β-CD: DCP (1:15–1:6). Based on preliminary evaluations, NSPs (D-NSP3) were optimized for size (412 ± 6.1 nm), polydispersity index (PDI) (0.259), zeta potential (ZP) (−10.8 ± 4.3 mV), and drug loading (DL) (88.7 ± 8.5%), and were further evaluated by in vitro release, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
3
5
0
Order By: Relevance
“…The solubility of BAR increased linearly with increasing the concentration of βCD as shown in Figure 1 , which confirmed AL-type system. 25 , 32 The slope value was smaller than 1, which denotes an inclusion complex with molecules in a 1:1 molar ratio (BRA: βCD). 26 The apparent stability constant, K1:1, was found to be 119.06 M −1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The solubility of BAR increased linearly with increasing the concentration of βCD as shown in Figure 1 , which confirmed AL-type system. 25 , 32 The slope value was smaller than 1, which denotes an inclusion complex with molecules in a 1:1 molar ratio (BRA: βCD). 26 The apparent stability constant, K1:1, was found to be 119.06 M −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The solution was solidified by cooling and then triturated in the mortar and pestle. 25 The resultant mass was crushed, then rinsed repeatedly with ultrapure water to remove the phenol by product, extracted in triplicate with absolute acetone, and then left to air dry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MM Ahmed et al reported the improved dissolution and aphrodisiac activity of sildenafil and tadalafil SDSDs using glycyrrhizin [36], [37], [31]. Spray-dried amorphous solid dispersion of diosmin in soluplus was prepared by MK Anwer and reported to show improved hepato-renoprotective and anti-oxidant properties [38].…”
Section: Of 21mentioning
confidence: 99%
“…One of the most relevant fields is drug delivery for cancer therapy [ 9 , 11 ], including breast cancer. In this aspect, CDNS showed improved anticancer drug effects both in vitro [ 12 , 13 ] and in vivo [ 14 ].…”
Section: Introductionmentioning
confidence: 99%